Performance of D-galactose for Protecting The Corrosion Rate of Aluminium Alloy 5052 (AA5052) in Acidic Environment - I Gusti Ayu Arwati; Sagir Alva; Wahyu Irwansyah; Ibdal Satar (Universitas Ahmad Dahlan, 2021)
The PEMFC systems are generally operated in acidic environment conditions. Consequently, the metal bipolar plate in the system can easily be corroded. Therefore, the PEMFC performance is decreased along with long-term operation. Based on this fact, a mitigation approach is needed to prevent the corrosion issue in the metal bipolar plate to maintain the PEMFC performance. This work tries to evaluate the corrosion rate of the aluminium bipolar plate before and after being deposited with D-galactose. The electrophoretic deposition (EPD) technique was used to deposit D-galactose on the aluminum surface. To evaluate the effect of D-galactose on preventing the corrosion rate, it was deposited on the surface of the aluminium (AA5052) bipolar plate. The EPD processes were performed by using a potensiodimic in 0.5 M H2SO4. The results show that the optimum EPD process condition was obtained at 0.5 g/l D-galactose for 20 minutes of electrophoretic deposition time. This work indicated that the D-galactose could reduce the corrosion rate of aluminium bipolar plate with an efficiency of 90.7%.